Heterojunctions and Nanostructures - Stavrou, Vasilios N. (IntechOpen, 2018)
The current book entitled Heterojunctions and Nanostructures is divided into two sections. In Section 1, the chapters are related to topological insulators where their theoretical aspects, their current experiments, and their applications are presented. A few presented topics are, among others, the topological phases of matter, band topology of insulators and also of Weyl semimetals, transport properties of 3D topological insulator quantum wires and the influence of disorder, transport properties of quasi-1D (and 2D) topological surface states, quantum coherence, and topological insulator thin-film Hall bar device. In Section 2, the chapters are related to light devices such as laser diodes and their fabrication techniques. This section includes, among others, topics such as semiconductor quantum nanowire laser diodes, solutions of Schrodinger equation in nanostructures, numerical methods, light-to-electricity conversion devices, photoexcited carrier transportation process in quantum wells and quantum dots, growth mode and characterization of heterostructure of large lattice mismatch, and photoionization cross section.